The influence of sorogan method in learning history to increase historical understanding and historical awareness - Muhammad Rijal Fadli; Ajat Sudrajat; Aman Aman; Kian Amboro (International Journal of Evaluation and Research in Education (IJERE), 2021)
The purpose of this study was to examine the influence of the sorogan method in history learning to improve students' historical understanding and historical awareness. The research method used a quasi-experimental nonequivalent control group design, and the sampling technique used a cluster sampling with a sample size of 96 students. Collecting data through observation, interviews, and tests of historical understanding and awareness. Meanwhile, data analysis to determine the effect and differences of the sorogan method to increase understanding and historical awareness using the independent sample t-test and N-gain score test. The results showed that there were a significant influence and difference between the two groups, namely the experimental and control classes based on the results of the independent sample t-test, the hypothesis H0 was rejected with a significance value of 0.000<0.05, further strengthened by the results of the N-gain score test which was included in the criteria low and medium. This means that there is an influence and increase from the implementation of the sorogan method on historical understanding and awareness and getting a positive response from teachers and students, because the sorogan method is student-centered, and the teacher acts as tutorship/mentorship.